Evaluation on knowledge management process in very small software companies: A survey - Basri, Shuib; O’Connor, Rory V. (2010)
Software development projects always involve knowledge intensive exchanges.Therefore, the influence of well-organized software development knowledge process could prevent organizations from suffering from the knowledge atrophy problem, i.e. loss of expert software development.In order to understand this issue, we have studied several factors (company’s strategy, communication, learning and documentation) that are related to knowledge management processes (KMP) in very small entities (VSE).An open and close ended survey was conducted in a variety of VSEs. Through statistical and content analysis for the research data, results indicate that KMP in VSEs are undertaken in an informal way.Furthermore this environment helped VSEs to easily create/share knowledge that assisted in mitigating the knowledge atrophy problem.